Does the Apoptosis Value of Cumulus Cells Play a Role in Rescue Oocyte in Vitro Maturation? - Tulay Irez; Sinem Ercan Dogan; Enver Ciraci; Saadet Busra Aksoyer; Muhammet Sait Toprak; Nurten Dayioglu; Onur Guralp (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: In this study, we aimed to investigate the role of the cumulus cell’s apoptosis parameter in the maturation of immature rescue oocytes.